First-principles molecular transport calculation for the benzenedithiolate molecule. (4th October 2017) - Rumetshofer, M; Dorn, G; Boeri, L; Arrigoni, E; Linden, W von der
Abstract: A first-principles approach based on density functional theory and non-equilibrium Green's functions is used to study the molecular transport system consisting of benzenedithiolate connected with monoatomic gold and platinum electrodes. Using symmetry arguments we explain why the conductance mechanism is different for gold and platinum electrodes. We present the charge stability diagram for the benzenedithiolate connected with monoatomic platinum electrodes including many-body effects in terms of an extended Hubbard Hamiltonian and discuss how the electrodes and the many-body effects influence the transport properties of the system.